Delay factors in the treatment of measles among residents of Osogbo, Osun state, Nigeria (2019)
Measles accounts for one of the vaccine preventable deaths among children in the world. Nigeria is one of the countries with a very high burden of measles where cases can even be under-reported partly due to delay in seeking health care. Utilizing the health belief model, the paper examines the delay factors in seeking prompt and accurate care when children have measles. The study utilized both qualitative and quantitative methods of data collection, using 400 self-administered copies of questionnaire to elicit information on delay factors and reliance of parents on use of herbs in the treatment of measles. Also, four sessions oj Focus Group discussions (FGDs) were conducted with parents. Data were analyzed and presented, using descriptive statistics such as percentages and chi-square. Findings revealed a significant relationship between socio-demographic factors and perceived treatment patterns of measles atX2(9) = 12.162, P=.0204. Furthermore, a significant level of association existed between parents ’ perceived traditional cause of measles, beliefs in-home remedy and use of herbs at X2 (16) =127.1, P=.000. Qualitative data revealed that most parents considered measles as a disease that can be managed at home, hence, they visit patent medicine stores to get drugs or use herbs and consequently visit hospitals when the child fails to recover. It concluded that parents ’ perceived causes and treatment practices in measles is far from adequate and hence, efforts should be geared towards sensitizing parents on how to reduce mortality and morbidity resulting from measles.